English Vocabulary Acquisition Patterns in Adult Tertiary L2 Learners - Giridharan, Beena (HETL, 2013)
The paper reports on a study that focused on analysing vocabulary learning patterns in adult tertiary second language (L2) learners. Research in the area of vocabulary development is unclear regarding the interrelationships among various aspects of lexical competence, learning, and production processes in L2 lexical acquisition. Models of vocabulary acquisition in English as a second language (ESL) are scarce and the lack often prompts L2 researchers to draw from first language vocabulary study models to correlate vocabulary developmental patterns. A theoretical linguistic framework for vocabulary development in L2 learners was first established through a review of the relevant L2 acquisition theories, linguistic schema theories, cognitive-psychological theories, and sociolinguistic theories which allowed the researcher to acknowledge their relevance to inferencing strategies in L2 vocabulary development. The study attempted to categorise the patterns of vocabulary inferencing strategies employed by the L2 learner; understand the role of context on the strategies; and examine the influence of teaching explicit inferencing strategies. Ultimately, the purpose of the study was to establish an L2 vocabulary model to account for the development of pre-receptive (PR) to productive (PV) processes of vocabulary development. The study employed a mixed-method research design. Procedural data analysis from phase one supported the development of a theoretical model of vocabulary development in L2 learners. The findings from the study may have pedagogical and theoretical implications for curriculum developers, instructors and policy makers in L2 tertiary English learning contexts.